Respuestas

2012-05-02T19:44:57+02:00

3x - 5(x/2 - 1) = 6

3x - 5[(x-2)/ 2] = 6

3x - [(5x-10)/2] = 6

(6x - 5x - 10)/2 = 6

6x - 5x - 10 = 12

x = 22

 

¡La mejor respuesta!
2012-05-02T20:00:23+02:00

buenas tardes.3x-5(x/2-1)=6
                     3x-5x-2=6
                      -2x=6+2

                       -2x=8

                       x=8/-2
                         x=-4                          comprobacion:3(-4)-5(-4/2-1)=6
                                                                                3(-4)-5(-4)-2=6
                                                                                -2(-4)=6+2

                                                                                 -2(-4)=8
                                                                                   -4=8/-2

                                                                                    -4=-4          saludos